Parent assessment of medical student skills in ambulatory pediatrics - Persson, Erika; Haines, Christina; Lang, Mia (Canadian Medical Education Journal, 2013)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: Partnership with parents is a vital part of pediatric medical education, yet few studies have examined parent attitudes towards learners in pediatric settings. Methods: Questionnaires were used to determine parent and student assessment of professional and clinical skills (primary outcome) and parent attitudes towards 3rd year medical students (secondary outcome) at the University of Alberta. Chi Square, Kendall’s Tau and Kappa coefficients were calculated to compare parent and student responses in 8 areas: communication, respect, knowledge, listening, history taking, physical examination, supervision, and overall satisfaction. Results: Overall satisfaction with medical student involvement by parents was high: 56.7% of all parents ranked the encounter as ‘excellent’. Areas of lesser satisfaction included physician supervision of students. Compared to the parent assessment, students tended to underrate many of their skills, including communication, history taking and physical exam. There was no relationship between parent demographics and their attitude to rating any of the students’ skills. Conclusions: Parents were satisfied with medical student involvement in the care of their children. Areas identified for improvement included increased supervision of students in both history taking and physical examination. This is one of the largest studies examining parent attitudes towards pediatric students. The results may enhance undergraduate curriculum development and teaching in pediatric ambulatory clinics and strengthen the ongoing partnership between the community and teaching clinics. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; –> <!–[endif] –>